Editing plant genomes with CRISPR/Cas9. (April 2015) - Belhaj, Khaoula; Chaparro-Garcia, Angela; Kamoun, Sophien; Patron, Nicola J; Nekrasov, Vladimir
Graphical abstract: Highlights: Cas9 is an RNA-guided DNA endonuclease innate to prokaryotic immune systems. CRISPR/Cas9 has recently emerged as a powerful genome editing tool. CRISPR/Cas9 has been successfully applied in many organisms, including model and crop plants. CRISPR/Cas9 is a cheap, robust and easy to implement technology. Abstract : CRISPR/Cas9 is a rapidly developing genome editing technology that has been successfully applied in many organisms, including model and crop plants. Cas9, an RNA-guided DNA endonuclease, can be targeted to specific genomic sequences by engineering a separately encoded guide RNA with which it forms a complex. As only a short RNA sequence must be synthesized to confer recognition of a new target, CRISPR/Cas9 is a relatively cheap and easy to implement technology that has proven to be extremely versatile. Remarkably, in some plant species, homozygous knockout mutants can be produced in a single generation. Together with other sequence-specific nucleases, CRISPR/Cas9 is a game-changing technology that is poised to revolutionise basic research and plant breeding.